Impact of Self Help Groups on the Empowerment of Rural Women: A Case of Kudumbasree Programme in Kerala (Indian Journal of Extension Education, 2011)
Empowerment can be defined as a multi-dimensional social process that helps people gain control over their own lives. In India, Self Help Groups (SHGs) have emerged as major instruments for women empowerment by fostering mobilization of rural women and facilitating their economic activities. Kudumbasree is a women oriented SHG based programme launched in 1998 by Government of Kerala to wipeout the absolute poverty in the state through a concerted action of community based organizations and local self governing bodies. Empowerment of rural women through group mobilization and collective action was the inherent objective of the programme. The study is based on the survey conducted in Kozhikode districtsof Kerala state to assess the impact of SHGs on the empowerment of rural women. It was found out that SHGs have contributed significantly to the empowerment of rural women. SHG members’ personal traits as well as group and social activities were the major determinants of empowerment.